2013
DOI: 10.1088/0004-637x/769/1/48
|View full text |Cite
|
Sign up to set email alerts
|

HERSCHEL/HIFI OBSERVATIONS OF A NEW INTERSTELLAR WATER MASER: THE 532-441TRANSITION AT 620.701 GHz

Abstract: Using the Herschel Space Observatory's Heterodyne Instrument for the Far-Infrared, we have performed mapping observations of the 620.701 GHz 5 32 -4 41 transition of ortho-H 2 O within a ∼1. 5 × 1. 5 region encompassing the Kleinmann-Low nebula in Orion (Orion-KL), and pointed observations of that transition toward the Orion South condensation and the W49N region of high-mass star formation. Using the Effelsberg 100 m radio telescope, we obtained ancillary observations of the 22.23508 GHz 6 16 -5 23 water mase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The 620.7-GHz (53,2-44,1) transition was detected as a maser by Neufeld et al (2013) towards Orion KL, Orion S and W49, with clear variability over 2 yr in the last source. The 620.7-GHz line appears to be pumped under physical conditions that are a subset of those that pump 22-GHz masers.…”
Section: Water Masers In Star-forming Regionsmentioning
confidence: 93%
“…The 620.7-GHz (53,2-44,1) transition was detected as a maser by Neufeld et al (2013) towards Orion KL, Orion S and W49, with clear variability over 2 yr in the last source. The 620.7-GHz line appears to be pumped under physical conditions that are a subset of those that pump 22-GHz masers.…”
Section: Water Masers In Star-forming Regionsmentioning
confidence: 93%
“…While the shocked region shows intense OH and H 2 O emission lines, the dense and warm environment of the Galactic Center region has a more diverse spectrum with other hydrides like NH 3 In the case of OH, mid-IR transitions with upper state energies, E u /k B of several 10 4 K can also be excited following the photodissociation of H 2 O by shock-generated UV radiation; this phenomenon, observed by Spitzer toward HH 211 and illustrated in Figure 10 Along with the normal (non-inverted) OH and H 2 O line radiation emitted by warm shocked regions, strong maser action is observed in several transitions : these include the 22 GHz 6 16 − 5 23 transition of H 2 O, frequently observed from outflow-driven shock waves along with several submillimeter water maser transitions (e.g. Neufeld et al 2013, and references therein), and the 1720 MHz transition of OH, a signpost of supernova-driven shock waves (e.g Frail & Mitchell 1998). Maser lines are typically characterized by small spots of emission, often unresolved even in long-baseline interferometric observations, narrow line width, and variability on timescales of months or less.…”
Section: Figurementioning
confidence: 94%
“…Their discovery of this feature gave rise to the present attempt to determine whether the 621 GHz feature might be linearly polarised. In a later search through the Herschel archives Neufeld et al (2013) also found similarly narrow 621 GHz emission features emanating from the Orion south condensation and the W49N region of high-mass star formation. By then, however, the Herschel mission was ending and a search for signs of polarisation in these features was no longer possible.…”
Section: Introductionmentioning
confidence: 75%
“…We thank D. Neufeld et al (2013) for alerting us to the presence of the 621 GHz transition prior to publication. HIFI has been designed and built by a consortium of institutes and university departments from across …”
mentioning
confidence: 99%